Analisis Efisiensi Pembangunan Berkelanjutan Antar Provinsi di Indonesia Menggunakan Data Envelopment Analysis (DEA) - Annisa Ananda; Fandy Triawan (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study analyzes the efficiency of sustainable development across 34 provinces in Indonesia during 2019-2023 using Data Envelopment Analysis (DEA) with an output-oriented Variable Returns to Scale (VRS) model. Inputs include regional government expenditure and labor force, while outputs comprise Gross Regional Domestic Product (GRDP) per capita, Human Development Index (HDI), and Environmental Quality Index (EQI). The analysis covers 170 decision-making units (DMUs). The results indicate that the national average efficiency score increased from 0.9357 in 2019 to 0.9639 in 2023, although disparities among provinces persist. North Kalimantan consistently achieved full efficiency throughout the study period. In addition, seven provinces achieved full efficiency at least once, namely Gorontalo, East Kalimantan, West Papua, Riau Islands, DKI Jakarta, DI Yogyakarta, and Bangka Belitung Islands. In contrast, Lampung, West Java, and East Nusa Tenggara recorded the lowest average efficiency scores. Potential improvement analysis reveals that GRDP per capita exhibits the largest performance gap, particularly in East Nusa Tenggara. These findings suggest that sustainable development efficiency depends not only on resource availability but also on the effectiveness of resource allocation and management.